An Outbreak of Acute Aflatoxicosis on a Chinchilla (Chinchilla Lanigera) Farm in Argentina - Gonzalez Pereyra, Maria Laura (2008)
Chinchillas are known to be very sensitive to aflatoxins and often a large number of animals die if an outbreak occurs. An acute aflatoxicosis outbreak in a chinchilla farm in Argentina is described in this study. A commercial feed suspected of causing the death of 200 animals was sampled. Nine livers from 9 dead chinchillas were analyzed for their macroscopic and microscopic characteristics through necropsy and histopathologic analysis. Aflatoxins B1, B2, G1 and G2 were determined in feed by thin layer chromatography. Gross macroscopic inspection of livers revealed general enlargement, pale-yellowish coloration, hypertrophy, blunt boards and decreased consistence. Size and color were remarkably different from a healthy organ. Histopathologic analyses of hepatic parenchyma showed severe and diffuse alterations by cytoplasmic vacuolation in hepatocytes. Sudan III staining confirmed the lipidic nature of the content present in the vacuoles. The feed was positive for AFB1 in quantities that exceeded the recommended levels. Histopathology confirmed that lesions were typical alterations associated with aflatoxins intake. Monitoring feed for mycotoxins is crucial to prevent outbreaks, to improve management practices and to diminish exposure risk of animals and humans to these harmful toxins.